Assyrian Historiography: A Source Study - Olmstead, A. T. (Albert Ten Eyck), 1880-1945 (Salt Lake City, UT : Project Gutenberg, 2004)
"Assyrian Historiography: A Source Study" by A. T. Olmstead is a scholarly historical account likely written in the early 20th century. The work delves into the sources and methodologies of historical writing in ancient Assyria, discussing the evolution and characteristics of Assyrian historical inscriptions and their implications for understanding Assyrian history. The opening of the book establishes the necessity of analyzing historical sources before constructing narratives of Assyrian history. Olmstead emphasizes different types of inscriptions, their accuracy, and their relevance to specific reigns, particularly highlighting the earliest periods of Assyrian historiography and the challenges faced due to the scarcity of detailed records prior to Tiglath Pileser I. He delineates the transition from Babylonian influences on Assyrian writing to the development of more structured annalistic forms during subsequent reigns, setting the stage for an in-depth exploration of the sources and critical methodologies that will follow in the remaining chapters. (This is an automatically generated summary.)
Release date is 2004-09-01
Produced by Arno Peters, David Moynihan Charles Franks and the Online Distributed Proofing Team
Keywords: Assyria -- History -- Historiography; Assyria -- History -- Sources